LECTURER PROFESSIONALISM IN THE LEARNING PROCESS - Sondang Purba (International Journal of Economy, Education and Entrepreneurship, 2021)
Lecturers are one of the human components in the learning process that play a very important role in the formation of potential human resources in the field of development. The role of lecturers in the learning process is felt to have a very large influence on changes in student behavior. The purpose of this study was to determine the professionalism of lecturers in the learning process, to determine the increase in the professionalism of lecturers in the learning process, and to determine what factors influence efforts to increase the professionalism of lecturers in the learning process. The method used is the Induction Method and the Deduction Method, while analyzing the data using techniques that are following the data, namely descriptive data. Lecturer's professional ability in making teaching preparations is in a good category. This is indicated by the lecturers having made teaching preparations with the correct procedure, namely by making teaching preparations referring to the applied curriculum, each sub-chapter discussion. Efforts made by lecturers to improve their professionalism are carried out by reading books, increasing education levels, holding regular meetings with fellow lecturers in the field of study, and conducting self-assessments